Analisis dan Simulasi Mesin Pencetak Keripik Telur Cumi - Ricky Tri Putra Ananda; Husman Husman; Yudi Oktriadi (Jurnal Inovasi Teknologi Terapan, 2026)
Squid egg chips are one of the typical foods of Bangka Belitung, which are still produced manually, making them inefficient in terms of time and energy. Manual production of squid egg chips in Bangka Belitung faces challenges in terms of efficiency and product consistency. This study aims to design and simulate a squid egg chip molding machine using a systematic approach based on the VDI 2222 method. The stages include needs analysis, concept development, technical design, and evaluation through load simulation using software such as Fusion 360 and MD Solid. The developed machine has an electric motor drive system, pulley and belt transmission, and main components such as a hopper, dough press screw, and dough mold. The simulation results show that the machine design works well and can withstand an operational load of up to 118.87 N, equivalent to ±12 kg. The system can be operated by one person with more efficient production time compared to the manual method. However, the dough cutting mechanism still needs improvement to achieve a uniform and aesthetically optimal chip shape.